(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
All functions within the company, regardless of its size and activity, meet with an extremely dynamic economy and an environment in which they perform many day-to-day activities. In that sense, procurement is no different. It no longer serves only the purpose of ordering goods or services at the request of production at the lowest possible prices. Today’s modern procurement systems offer solutions, improvements and thoughts on all aspects of business operations in which they are involved. There is a special emphasis on the dynamic resolution of challenging situations, which lies in unpredictable circumstances and crisis. The procurement department always works closely with other functions that directly affect production, and this is where extremely dynamic, high-quality and timely communication is expected. Communication with functions within the company is followed by communication with partners, where procurement becomes a sort of link between production and suppliers. Members of the procurement team are in most cases representatives of their companies, and it is based on their communication skills, behaviour and decisions that the image of the company is created among partners. Quality and timely communication of procurement team members with partners can play a key role for the continuation of production in turbulent market situations. Managers must organize all procurement processes in a quality manner, as well as motivate, educate and reward members of the procurement department. With their comments, opinions, advice and experience, partners offer an additional perspective, solution and an alternative path in the further planning of steps which would help achieve all of company’s objectives. Experienced management, especially in times of crisis, use all possible information to make quality decisions, but also learn from these situations in order to make all possible preparations in regular business operations to minimize the shock that a new crisis could cause. The theoretical part of the paper will present a description of the concept of procurement business, management and crisis management, business and crisis communication, creating partnerships, and maintaining the company’s image. The empirical research, conducted through questionnaires which were filled in by employees from the procurement department in the Republic of Croatia, provides us with answers about the importance of partnerships, with a special emphasis on the current coronavirus pandemic. In conclusion, we have explained proposals for improving and maintaining partnerships in the procurement business during crisis, as well as in regular business situations.